Zakat from an Islamic Economic Point of View - Nurhendi, Sigit (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2023)
The purpose of this paper is to describe zakat from an Islamic economic standpoint utilizing qualitative methods and a literature review. Because zakat has enormous potential from an Islamic economic standpoint, it deserves more attention from the government and the broader public, as does the urgency of zakat in improving people's welfare. Finally, zakat can be a source of foreign exchange for the country as well as an alternate solution for communal welfare. As a result, zakat has tremendous economic worth in addition to religious value